A Comparative Study of Primary School Teachers' Educational Assessment Competencies in Private and Public Schools in Hanoi City: Current Status and Influencing Factors - Huong, Do Thi; Huong, Tran Thi Thu (VNU Journal of Science: Education Research; Vol 41 No 4, 2025)
This study aims to analyze the differences in educational assessment competencies among primary school teachers in private and public schools in Hanoi, as well as to identify factors influencing these competencies. A survey was conducted involving 286 teachers from five selected public and private primary schools to evaluate their educational assessment capabilities. The findings highlight significant differences in three key competency areas: assessment planning, development of assessment tools, and self-directed learning in educational assessment. Conversely, no notable differences were observed in three other areas, which include the implementation of assessments, usage of assessment results, and feedback processes. Additionally, the results reveal that primary school teachers excel in certain practices such as observing, assessing, praising, and encouraging students, alongside effective communication and engagement with students to facilitate their learning progress. The study further identifies various factors that impact teachers' competencies in educational assessment, providing valuable insights for the design of training programs aimed at enhancing primary school teachers' assessment capabilities.